PENGARUH PENAMBAHAN SARI BUAH SIRSAK TERHADAP SIFAT SENSORIS MINUMAN ISOTONIK AIR KELAPA (Cocos nucifera L.) - Lempoy, Wulan Kristie; Mandey, Lucia Cecilia; Kandou, Jenny E. A. (Fakultas Pertanian, Universitas Sam Ratulangi, 2020)
ABSTRACTThis study aims to determine the proportion addition of soursop juice and analyze the chemical contents of isotonic drink from mature coconut water (Cocos nucifera L.) This research was conducted by adding 100 ml, 200 ml, and 300 ml of soursop juice to 1000 ml of coconut water. The test parameters were organoleptic tests using hedonic methods including flavor, taste, and turbidity. The best treatment was followed by chemical testing including sodium, potassium, acidity (pH), total acid and total sugar. The result of organoleptic test showed that 1000 ml of coconut water without soursop juice addition has a value of 2,73 (neutral), while the addition of 100 ml soursop juice has a value of 3,43 (neutral), the addition of 200 ml soursop juice has a value of 3,54 (like), and the addition of 300 ml soursoup juice has a value of 3,71 (like). In conclusion, the best result is the addition of 300 ml soursop that had a mineral content of sodium as much as 469,36 mg/kg, potassium as much as 2014,45 mg/kg, pH 4,65, total acid 0,54% and total sugar 6,33%.Â Keywords: Isotonic Drinks, Soursop Juice, Coconut Water